Case Study : Anas Hq / Nurul Syazwani Anuar - Anuar, Nurul Syazwani (2021)
ANAS HQ is located at No.40,Jalan Astaka U8/84A,Bukit Jelutong, Seksyen U8, 40150,Shah Alam, Selangor.I pick this location as it is an industrial places and is at a strategic place.This business focus on cosmetics,f&b and scarf. The cosmetics that they produce is beauty sponge,foundation, lipmatte, eyeliner and etc. ANAS HQ also produce many design of scarf and food . ANAS Cosmetics was established in August of 2017 when they discovered a problem among Asian women in finding the right shade that matches their skin tone & they use that as a fuel of inspiration for their brand. All of their products are made to match the Asian women for the sole purpose to lift out the major issue that they encounter on a daily basis which is matching shade.They put their focus into being the first local product that goes international with a quality that aligns with the global standard which ANAS Cosmetics also is one of the local makeup brand in SaSa Malaysia (owned by international Hong Kong Company) They put a lot of thoughts, research and hard work into their products with hope to fulfil women’s desire in wearing make up that truly suit their skin flawlessly.Anas Zahrin, the Creative Director behind the brand has always been the person who seeks solution to ease every women so that they can enhance their beauty by make up. Not only that, their motto Show Your True Colors definitely aligns with the direction of creativity that Anas Zahrin lead.Their major purpose is to fulfil the demand of the market in producing high quality products with an affordable price while they stand tall amongst the international brands.